Foldable multifunction hand trolley / Muhammad Luqman Fahmi Mohd Zaki and Najibah Ab Latif - Mohd Zaki, Muhammad Luqman; Ab Latif, Najibah (School of Mechanical Engineering, 2022)
Mechanical Engineering students of semester 4 were given a task to manufacture a product to help or ease people in solving everyday problems. From the data obtained, people are having a problem carrying or transporting loads of bigger shape or dimensions. The objective of this project is to design and fabricate a multifunctional trolley and can be used with 4-wheel mode and 2-wheel mode. This project is also to analyse the multifunction hand trolley affected to the applied load using simulation software. This concept will be generated by referring to existing products in the market based on the characteristic and criteria. Some manufacturing steps will be included in this proposal like research and literature review. There will be several manufacturing processes to fabricate this project like measuring, cutting, welding, and finishing. Upon the completion of this fabrication, an in-depth understanding will be gained and improvement on ability to write an excellent proposal for engineering design fabrication which then can assist fellow students in their future professional environment in the engineering world.